2023
DOI: 10.1111/aab.12836
|View full text |Cite
|
Sign up to set email alerts
|

Chlorophyll a fluorescence during flag leaf senescence of field‐grown winter wheat plants under drought conditions

Abstract: Improving wheat grain yield plays a significant role in ensuring global food security.Wheat production could be increased by the genetic improvement of wheat genotypes where delayed senescence with enhanced post-anthesis capacity and staygreen traits could have an important role. In this study, chlorophyll a fluorescence (ChlF) rise kinetics from the early until late senescence of flag leaves, grain yield and other agromorphological characteristics were compared for three winter wheat advanced lines under nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Further, the varieties with the highest grain yield (Bubnjar, Silvija, and Rujana) showed an increase in PI ABS, or a slight decrease in the case of Silvija, from the 6th to the 7th measurement, compared to other varieties showing a pronounced decrease between these two measurements. In the previous research, it was reported that longer integrity of functional PSII units and extended preservation of the optimal level of energetic connectivity among PSII units during grain filling resulted in better agronomic performance [28]. Higher grain yield resulted from increased 1000 kernel weight, which could be related to the source/sink ratio established during the early grain-filling stage [74].…”
Section: Vegetative Season 2022/2023mentioning
confidence: 96%
See 1 more Smart Citation
“…Further, the varieties with the highest grain yield (Bubnjar, Silvija, and Rujana) showed an increase in PI ABS, or a slight decrease in the case of Silvija, from the 6th to the 7th measurement, compared to other varieties showing a pronounced decrease between these two measurements. In the previous research, it was reported that longer integrity of functional PSII units and extended preservation of the optimal level of energetic connectivity among PSII units during grain filling resulted in better agronomic performance [28]. Higher grain yield resulted from increased 1000 kernel weight, which could be related to the source/sink ratio established during the early grain-filling stage [74].…”
Section: Vegetative Season 2022/2023mentioning
confidence: 96%
“…For example, according to the recent research by Kubar et al [26], fertilization with nitrogen resulted in increased leaf area and significantly prompted the photosynthetic rate, which resulted in an improvement in grain yield. In addition, plants exhibit genetic variations in photosynthetic response under abiotic and biotic stresses [27,28]. When plants are exposed to disease stress factors, especially during the flowering stage, disruption in the photosynthetic apparatus can occur, causing a decrease in plant productivity and overall grain yield [29].…”
Section: Introductionmentioning
confidence: 99%